Putting the shameful body to death: some critiques and a way forward in the soteriology of shame. (October 2019) - Cozens, Simon; Ochs, Christoph
The concepts of 'honour and shame' have emerged in contemporary missiological discourse as a key tool for ministry among 'shame cultures'. While a recognition of different cultural values is an important step towards contextualisation, the soteriological models presented in these discussions are primarily based on a number of hidden assumptions which require further investigation: that shame is overcome by an outpouring of honour; that shame is a problem between humanity and God; and that the 'honour system' of this world is a viable model in which to locate salvation. We review these assumptions and instead propose an understanding of salvation for shame based on the rejection of honour, the subversion of shame, the death of the shameful body and rebirth in new community.